STUDI KASUS TEKNIK RADIOGRAFI VERTEBRAE LUMBOSACRAL PADA KLINIS SUSPECT FRAKTUR DI INSTALASI RADIOLOGI RSI SULTAN AGUNG SEMARANG - Lukluatin Nabila,; Anshor Nugroho,; Ayu Mahanani, (Journal of Innovation Research and Knowledge, 2025)
Radiography examination of the lumbosacral vertebrae in cases of suspected fractures at the Radiology Installation of Sultan Agung Islamic Hospital uses Antero-Posterior (AP), Lateral projections, and additional Lateral Flexion and Extension projections. One of the examinations that can be used to establish a fracture diagnosis is radiography examination of the lumbosacral vertebrae with Antero-Posterior (AP), Lateral, RPO and LPO or RAO and LAO projections. This study aims to determine the technique of radiography examination of the lumbosacral vertebrae and the role of using Lateral Flexion and Extension projections in radiography examination of the lumbosacral vertebrae in cases of suspected fractures. Method: This type of research applied qualitative descriptive with a case study approach on the technique of radiographic examination of the lumbosacral vertebrae in clinical suspect fractures at the Radiology Installation of Sultan Agung Islamic Hospital of Semarang which was conducted in November 2024 - January 2025. The subjects in this study consisted of three Radiographers, one Radiology Specialist, and one Sending Doctor. Data collection was carried out using observation, interview, documentation, and literature methods. Data analysis used data reduction by simplifying the data after the data was collected, data presentation by forming a description in the form of a coding graph and drawn into conclusions. Results: Lumbosacral vertebrae radiography techniques include patient preparation, preparation of tools and materials, and lumbosacral vertebrae examination techniques in clinical suspect fractures using anteroposterior (AP), lateral, lateral flexion and extension projections. The role of lumbosacral vertebrae radiography examination with lateral flexion projection in clinical suspect fractures is to see the shift of the vertebrae bone to the front or commonly called listhesis, to see whether there is stability in the bone. In the lateral extension projection in clinical suspect fractures, it is the same as the lateral flexion projection, namely to see the shift of the vertebrae bone to the back, see the stability of spondylolisthesis more clearly, and assess the stability of the joint which will determine further actions such as installing stabilization. Conclusion: Lateral flexion projection to see the shift of the vertebrae bone to the front or commonly is called listhesis, to see whether there is stability in the bone. Lateral extension projection aims to see the shift of the vertebrae bone to the back, to see the stability of spondylolisthesis more clearly, and to assess the stability of the joint which will determine further actions such as installing stabilization